2004
DOI: 10.1021/cg034187s
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cocrystals of 2-Amino-3-nitropyridine with Benzenesulfonic Acids for Second-Order Nonlinear Optical Materials

Abstract: Noncentrosymmetic and chiral cocrystals were prepared from 2-amino-3-nitropyridine (2A3NP) and achiral benzenesulfonic acids (Ar-SO 3 H), which were designed for second-order nonlinear optical materials. Both components are commonly crystallized in 1:1 ionic forms of 2A3NPH + ‚Ar-SO 3 -. The molecular packings of cocrystals are controlled by the aromatic-aromatic interactions as well as multidirectional ionic and hydrogen bonds between the 2A3NPH + cations and the sulfonate anions. The crystal of 2A3NP with p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…Despite those structural similarities, there is one important difference -the absence of the herringbone pattern, which could cause the crystallization of the selenate compound in the centrosymmetric space group. This observation is in good agreement with the assumption that the arrangement of 2-amino-3nitropyridinium cations in the herringbone motif is responsible for the formation of the non-centrosymmetric framework (Pecaut et al, 1993;Fur et al, 1998;Morel et al, 2002;Koshima et al, 2004).…”
Section: Structural Datasupporting
confidence: 87%
See 1 more Smart Citation
“…Despite those structural similarities, there is one important difference -the absence of the herringbone pattern, which could cause the crystallization of the selenate compound in the centrosymmetric space group. This observation is in good agreement with the assumption that the arrangement of 2-amino-3nitropyridinium cations in the herringbone motif is responsible for the formation of the non-centrosymmetric framework (Pecaut et al, 1993;Fur et al, 1998;Morel et al, 2002;Koshima et al, 2004).…”
Section: Structural Datasupporting
confidence: 87%
“…2-Amino-3-nitropyridine (2A3NP) with electron donor (NH 2 ) and electron acceptor (NO 2 ) groups is a good moiety for high molecular polarizability. Several non-centrosymmetric organic-inorganic hybrid compounds, including the 2amino-3-nitropyridinium cations as nonlinear optical entities, have been discovered (Nicoud et al, 1997;Fur et al, 1998;Koshima et al, 2004;Chen et al, 2014). Furthermore, such acid-base compounds were found to undergo multiple structural phase transitions related to the dynamics of organic cations or inorganic anions (Czarnecki & Małuszyń ska, 2000;Pająk et al, 2006) and were found to possess peculiar physicochemical properties, such as high proton conductivity (Susan et al, 2003;Wojnarowska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…14 The task of realizing efficient NLO-phores (non-linear optical chromophores with large b) 15,16 often requires multi-step synthetic processes, which, when handicapped with low yields, consume significant amounts of time and resources to generate sufficient material to screen for SHG active multi-component salts and cocrystals. [17][18][19][20][21] On the other hand, screening a large number of coformers is essential because it increases the probability of finding a suitable counterion or coformer that renders appropriate orientation of an NLO-phore to achieve optimal phase matching for large bulk SHG activity. 1,22 Further, the effect of a counterion or coformer in steering the NLO-phore into a centrosymmetric or non-centrosymmetric lattice is so unpredictable that the outcome of using a particular coformer cannot be generalized to any other structurally related molecules.…”
Section: The Bigger Picturementioning
confidence: 99%
“…Elemental analysis: found, %: C 23.23, H 6.85, N 13.53. Calcd for C 6 Synthesis of (APDPH 3 )$(pipH 2 ) 0.5 (5) A mixture of 0.2192 g APDPH 4 (1 mmol), 0.0971 g pip$6H 2 O (0.5 mmol) and 0.5 mL distilled water was sealed in a small centrifuge tube and then heated at 80 C for 3 d. Colourless crystals for single-crystal diffraction analysis were obtained. Yield: 52% (based on APDPH 4 ).…”
Section: Synthesis Of (Aedph 2 )$(Piph 2 )$H 2 O (3)mentioning
confidence: 99%